(untitled) (Estudios Gerenciales, 2012)
Organizations need well trained employees in order to maintain a competitive advantage. The purpose of this paper is to describe current training practices in Peru and to provide recommendations for improving organizational performance. This paper also aims to set priorities for future research work. Human capital theory and contributions on need assessment, and training planning, implementation and evaluation served as theoretical framework. This is a cross-sectional, exploratory study that used information from surveys conducted in 24 Peruvian companies. The findings reveal a strong interest in training, particularly with regard to the improvement of competencies, preference for face-to-face training, and the use of reaction evaluation methods. The recommendations include, among others, improving the provisions for internal support, policies, technology, behavioral evaluation, and resources.